The extent to which mathematics instructional practices in early childhood education in Zimbabwe relate to or make use of children's experiences. - Mutemeri, Judith; Mugweni, Rose (2016)
The aim of the study was to establish the extent to which mathematics instructional practices in early childhood education relate to or make use of children's experiences. The major question that guided the study was: In which ways do early childhood teachers use children's out-of-school strategies and everyday experiences in teaching mathematics? The study was conceptualised within a constructivist framework, in which meaningful mathematics instruction for young learners capitalises on their prior knowledge and the ways they solve their daily mathematical problems, and promotes active thinking in the process of making meaning. The study was qualitative, involving classroom observations using videotapes, interviews with teachers and questionnaires with Grade 1 and 2 teachers in a district of Masvingo, Zimbabwe. The major findings of the study were: teachers used children's knowledge minimally when introducing lessons and failed to build on children's knowledge throughout the lessons. There were observably low motivation and low performance by children during lessons. The ramifications of the study for policy and practice are discussed.